Incidence and survival of sinonasal adenocarcinoma by site and histologic subtype*. (3rd April 2018) - Kılıç, Suat; Samarrai, Ruwaa; Kılıç, Sarah S.; Mikhael, Mina; Baredes, Soly; Eloy, Jean Anderson
Abstract: Objective: To determine the incidence and survival of sinonasal adenocarcinoma (SNAC) by subsite and histologic subtype. Study design: Retrospective database review. Methods: Using the SEER database, we performed a retrospective analysis, identified cases of SNAC diagnosed between 1973 and 2013 and analyzed demographic, histopathology, clinicopathology, and determinants of disease specific survival (DSS). Results: A total of 746 patients with SNAC were identified. Median age at diagnosis was 64 years. Overall incidence was 0.44 per million, and was higher among blacks (O.R.:1.10–2.07:1) and males (O.R.:1.38–2.06:1). Nasal cavity (41.5%) was the most common site, followed by maxillary (26.5%), and ethmoid (17.4%) sinuses. Intestinal-type adenocarcinoma was less likely than Adenocarcinoma not otherwise specified (ANOS) to be found in the maxillary sinus (8.8% vs. 30.6%, p  < .05). Surgery alone (48.56%) was the most common treatment modality, followed by surgery and radiotherapy (RT) (32.5%), and RT alone (11.6%). DSS at 5, 10, and 20 years were 63.8%, 57.6%, and 47.0%, respectively. DSS was higher for nasal cavity SNAC, lower grade, lower stage, and those receiving surgery only. Conclusions: SNAC is more common among men and blacks. Incidence has not changed significantly in the past 40 years. Survival varies with grade, stage, histology, subsite, and treatment.